Analysis of The Advantages of Microsoft Teams as A Corporate Communication Tool in Supporting Employee Performance - Melati, Ria (Eduvest - Journal of Universal Studies, 2025)
This study aims to evaluate the advantages of Microsoft Teams' features as a corporate communication tool that supports employee performance. The research methodology includes literature analysis and a Systematic Literature Review (SLR). Through SLR, this study collects, reviews, synthesizes, and summarizes various relevant studies on the topic. The research process begins with searching for related articles using the Publish or Perish application, which accesses the Scopus database with the keyword "Microsoft Teams Application as a Corporate Communication Tool in Supporting Employee Performance," limited to articles published between 2020 and 2024. The findings indicate that Microsoft Teams offers several key advantages in workplace communication and collaboration, such as comprehensive integration with third-party applications, flexibility and scalability, complete communication features, and high security and compliance standards. The use of Microsoft Teams has been proven to increase employee productivity by up to 20%, enhance employee engagement, and facilitate remote meetings, online training, and cross-department collaboration.